A bibliometric and visual analysis of the impact of senescence on tumor immunotherapy - Liu, Zixu; Mao, Yuchen; Wang, Shukai; Zheng, Haoyu; Yang, Kangping; Yang, Liang; Huang, Peng (Frontiers in Immunology, 2025)
BackgroundRecently, many studies have focused on the relationship between senescence and immunotherapy in cancer treatment. However, relatively few studies have examined the intrinsic links between the three. Whether these studies can act synergistically in the fight against cancer and the specific links between them are still unclear.MethodsWe extracted, quantified, and visualized data from the literature (n = 2396) for the period 2004-2023 after rigorous quality control using citespace, GraphPad Prism, the R software package, and VOSviewer.ResultsLinear fit analyses were generated to predict the number of annual publications and citations as a function of the top-performing authors, journals, countries, and affiliations academically over the past two decades such as Weiwei, Aging-us, China, and the UT MD Anderson Cancer Center. Vosviewer-based hierarchical clustering further categorized study characteristics into six clusters, including two major clusters of immunotherapy research, immunosenescence-related research factors, and timeline distributions suggesting that cellular senescence and tumor progression is a relatively new research cluster that warrants further exploration and development. Study characterization bursts and linear regression analyses further confirmed these findings and revealed other important results, such as aging (a = 1.964, R² = 0.6803) and immunotherapy (a = 16.38, R² = 0.8812). Furthermore, gene frequency analysis in this study revealed the most abundant gene, APOE, and SIRT1-7 proteins.ConclusionThe combination of aging therapies with tumor immunotherapies is currently in its preliminary stages. Although senescence has the greatest impact on ICB therapies, mechanistic investigations, and drug development for APOE and sirt1-7 (Sirtuins family) targets may be the key to combining senescence therapies with immunotherapies in the treatment of tumors.